(untitled) (Research, Society and Development, 2022)
Introduction: In the activities of the Oil & Gas production line, the common accidental scenario is the oil spill. In the offshore area for this scenario, the control measures imposed are strict to avoid and mitigate the effects of impacts on sensitive environments and communities that stratify resources for their survival. The Santos Basin, the pre-salt production area, has been showing excellent results since its entry into production in terms of controlling oil spill scenarios and their derivatives, as well as their consequences. The study aims to demonstrate that despite the effective increase in oil and gas production in the Santos Basin compared to production in previous years, the events related to oil spills were inversely proportional, and thus presents some instruments that have corroborated their controls. Methodology: The study was developed by qualitative descriptive exploratory research using as a reference’s studies published in full, in Portuguese and published in the period between 2016 and 2021, extracted from magazines specialized in the environment and in the production and drilling of oil. Results and Discussions: The Santos Basin did not present to the world only large numbers regarding the production potential of its fields, but numerous challenges related to ultra-depths, sensitivity of marine environments never explored, long distances from the coast. To avoid damage from possible leaks, actions were taken such as robust Emergency Plans supported by effective contingency logistics, well-structured communication and training flows, as well as attention to measures related to operational safety and the integrity of the facilities. Conclusion: The involvement of several competent public and private sectors in the determination of actions to control possible leaks and the mitigation of their impacts proved to be effective in the production of the Santos Basin.